Assessment of forest fire risk in the atlantic coast of Uruguay - Ramos, Virginia Myrian Fernández (2019)
Forest fires are complex events which set economic goods, ecosystem services, human lives at risk, as well as produce unwanted transformations in the landscape. The perspectives derived from Climate Change foresee an increase in the frequency of these events as well as a greater severity. Uruguay is a country dominated by the prairie ecosystem; however, forestation has been promoted at different times: first for sand dune fixation and subsequent urbanization, later for the production of cellulose. The Uruguayan Atlantic coastal zone is one of the most important tourist destinations in the country. There, forests were implanted with the purpose of fragmentation and sale of plots of land which have created an urban forest interface associated with seaside resorts landscape, most times without appropriate care. Frequent wildfires in this area underline the need for risk reduction strategies for the region. Growing sprawl housing generates more complex situations in wooded areas not easily accessible. Residence localization options and urban sprawl structure natural environments, inducing and affecting biodiversity, and consequently modifying the quantity and quality of fuel. In turn, natural environment quality and landscape influence the location housing decision and participate in the process of urban expansion. This interface creates vulnerability; it is a combined effect of exposure to danger, sensitivity of the different components of the territory and society, and the degree of resilience. The purpose of this investigation is to know forest fire risk by analysing the interaction between the hazards, identified through forest fires themselves, specifically analysing areas burnt in those events. Vulnerability was defined as residence exposure in forested areas. The first four chapters of the thesis describe and analyse the occurrence of forest fires at national level, the forestation evolution in the country and the characteristics of the coastal zone, scenario of the problem studied. In the fifth chapter remote sensing techniques and indexes were applied to discriminate burned areas. The topic is complemented with the calculation of occupancy, adjacency and dispersion indicators of the dwellings, to evaluate their exposure through GIS. Chapter 6 incorporates the social perception about wildfire risk in this modified area and to know how public participation would work for its reduction. The opinions were collected through workshops with authorities participation from different agencies as well as stakeholders to approach the subject in one of the most populated municipalities . Also an online survey of the tourism agencies in the area was applied. The second last chapter explores the existing regulations regarding risk and land planning to know how much this problem is included in public policies. Finally, Chapter 8 presents the main findings and conclusions of the research that could contribute to improving public policies and actions to reduce the risk of forest fires on the Atlantic coast. With a weak and outdated policy, some outcomes seem to be inevitable. If forest fires and landscape are changing, the risk management strategy for forest fires and thus the regulations should change. Also, having a single strategy does not seem to be the most convenient. The strategy based solely on the extinction of fire ignores a fundamental aspect that refers to the vegetation that benefits from the fire for its propagation and raise the risk of fire. Meanwhile, a strategy that integrates the extinction with preventive actions of the forest management becomes more effective to mitigate the risk. It seems necessary to move towards sustainable forest management to minimize the socio-economic impacts of fire and maximize its ecological benefits. An intelligent forest fire management implies planning and carrying out activities in a fully integrated manner, both at the vegetation and landscape levels. This kind of management aims to control the fire regime by intervening in the vegetation as fuel, to promote environments more resistant to fire and less flammable.